Pengaruh Adhocracy Culture dan Komitmen Organisasi Terhadap Knowledge Sharing Dengan Organizational Citizenship Behavior Islamic Perspective Sebagai Variabel Mediasi - Nuraini, Ninda; Rahmayanti, Dini (Jurnal Manajemen Bisnis Syariah, 2025)
This study was conducted to determine the effect of Adhocracy Culture and Organizational Commitment on Knowledge Sharing with Organizational Citizenship Behavior Islamic Perspective (OCBIP) as a Mediating Variable (Study on Batik UMKM Employees in Batik Pilang Tourism Village). The research method used is quantitative method with proportional random sampling technique. Data collection in this study was carried out by distributing questionnaires to employees of batik UMKM in the Batik Pilang Tourism Village. The population and sample were 82 employees. From the results of the analysis conducted, one, Adhocracy Culture has a significant positive effect on Knowledge Sharing. Two, Organizational Commitment has a significant positive effect on Knowledge Sharing. Three, Organizational Citizenship Behavior Islamic Perspective (OCBIP) has a significant positive effect on Knowledge Sharing. Four, Adhocrcay Culture has a significant positive effect on Organizational Citizenship Behavior Islamic Perspective (OCBIP). Five, Organizational Commitment has a significant positive effect on Organizational Citizenship Behavior Islamic Perspective (OCBIP). Six, Organizational Citizenship Behavior Islamic Perspective (OCBIP) is able to mediate the effect of Adhocracy Culture on Knowledge Sharing. Seven, Organizational Citizenship Behavior Islamic Perspective (OCBIP) is able to mediate Organizational Commitment to Knowledge Sharing. Batik UMKM in Pilang Batik Tourism Village are expected to be able to increase the level of knowledge sharing always increasing organizational commitment